Конституционность Отмены Обязательных Расходов На Здравоохранение: Попытка Либерализации Отрасли Здравоохранения (The Constitutionality of the Abolition of Mandatory Healthcare Expenditures: An Attempt to Liberalize the Healthcare Sector) - Triyunarti, Wiwin; Farhani, Athari; Tinambunan, Wahyu Donry; Azizah, Faiqah Nur; Rahmawati, Dheya (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
Health expenditure is a fundamental obligation of the state, as healthcare is an essential public service that must be provided to its citizens, particularly to lower- and middle-income groups. The allocation of the health budget, both in terms of amount and percentage, cannot be altered without undergoing a legislative process and must comply with minimum constitutional requirements. With the enactment of Law No. 17 of 2023 on Health, the provision mandating compulsory health spending has been removed. This change represents a significant regression compared to the previous Law No. 36 of 2009 on Health, which guaranteed a fiscal allocation of at least 5% of the national budget (APBN) for the health sector. The research employs a normative legal method, drawing on conceptual and statutory approaches. The findings indicate that, according to the World Health Organization (WHO), mandatory health spending of only 4–5% of the Gross Domestic Product (GDP) is tough to sustain. Therefore, governments are encouraged to allocate at least 5% of their GDP to mandatory health spending. Indonesia’s decision to eliminate this mandatory spending poses a substantial risk of neglecting public health financing, especially for vulnerable groups. Ultimately, this may hinder adequate access to healthcare services and reduce both the quantity and quality of health programs for the general population.